Factors Determining Voluntary Counseling and Testing (VCT) for the Human Immunodeficiency Virus (HIV) among Low Income Women: Focus Group Findings from Rural, Urban, and Peri-Urban Women Groups in Lilongwe District-Malawi - Marisen Mwale (Journal of Basic & Applied Sciences, 2014)
Most high prevalence sub-Saharan African countries tend to over-emphasize fidelity and condom use as major preventative measures relative to HIV and AIDS prevention. Studies of behavior change that focus exclusively on these strategies of most interest to the prevention community bias examinations of behaviour change downward by ignoring other potentially effective ways of limiting the epidemic. Regardless of the dearth in efficacy, as well as tolerance bottlenecks; the prevailing debate over provider initiated testing in Malawi may depict a shift towards HIV Testing and Counseling (HTC) in Acquired Immunodeficiency Syndrome (AIDS) prevention. The current study examines factors that determine VCT uptake among low income women in the Lilongwe district. A qualitative paradigm- the Focus Group Discussion (FGD) was utilized to inform the study. Convenient sampling was used to isolate three women groups namely; St John Nsamba, Women of Action, and National Association of People Having AIDS in Malawi (NAPHAM) support group as participants. The first two groups were sampled as primary groups, the former representing the urban domain with the later representing the rural domain respectively. Between 10 – 15 participants from each group, approximately within the age category 20-49 were involved. Findings suggest socio-cultural gender stereotypes inhibiting negotiating testing with partners as well as the social comparison or optimistic bias motivating ordinary women to underestimate their risk of contracting HIV relative to significant others as major barriers. Recurrent illnesses was considered the major motivator, downplaying the empirical impression about access to treatment as major incentive. The methodical conclusion drawn from the study is that VCT has the potential to mitigate the spread of HIV but for the preventative measure to be successful there is need to surmount various ethnographic and socio-cultural constraints currently impeding the intervention.